Proyecto de negocio 3D Lab & Café - Hurtado de Mendoza Barra, Percy Enrique (2019)
The present business project shows the feasibility to install a new experience in the city of Lima that merges the concept of cafeteria with the opportunities offered by 3D printing. We are bringing this technology closer to the everyday life within an innovative environment which stimulates creativity. Our research has showed that there is an unsatisfied demand and a great interest in university students who need a space to carry out their 3D printing work. It was also evidenced that for the general public there is not much knowledge about this technology. We will have to work in order to spread the opportunities that this new tool could bring to them. The purpose is to stop being consumers and to become creators. The digital manufacturing centers of universities as well as companies are beginning to invest in this technology causing a positive development in the domestic market. Also this business model is already profitable in other countries. Finally, the financial analysis shows a very good return on investment, so it is concluded that our 3D Lab & Cafe business project is viable.